Δ18O analysis of Atactodea striata: evaluating a proxy for sea-surface temperature and shellfish foraging from a prehistoric rockshelter in Palau, Micronesia. (December 2015) - Jew, Nicholas P.; Fitzpatrick, Scott F.
Abstract: In this research we examined the isotopic signatures of sequential growth increments from 10 modern and 11 archaeological Atactodea striata shells (21 shells with a total number of 112 samples). Modern shells and recorded sea surface temperature measurements (SSTs) were used to evaluate the geochemistry of A. striata as a suitable candidate for recording ambient SST. Pairing oxygen isotopes and recorded SST of modern samples with x-ray diffraction (XRD) allows the identification of the biomineralogical composition of A. striata and provides the necessary information to select the most appropriate carbonate temperature equation to convert oxygen isotope values to estimated SST. This SST conversion was then applied to isotopic data from 11 shells recovered from a ~ 1700 year old component at the Chelechol ra Orrak site in Palau, Micronesia. We discuss the biomineralogical composition of A. striata, modern and prehistoric sea-surface temperature variation, and the importance of using modern shellfish analogues in conjunction with archaeological samples for paleoenvironmental reconstructions. Isotope values from modern A. striata, when converted using Grossman and Kus' (1986) temperature conversion equation, was found to be similar to measured SST. Estimated SST from archaeological shells showed that the mean SST at 1700 cal. BP were similar to modern values, but SST ranges may have been slightly greater. Highlights: δ 18 O analysis A. striata Aragonite biomineralogical composition of A. striata SST for 1700 cal BP at Chelechol ra Orrak were similar to modern